Particle dynamics and fluxes in canyons and open slopes of the southern Cretan margin (Eastern Mediterranean). (December 2018) - Karageorgis, A.P.; Kontoyiannis, H.; Stavrakakis, S.; Krasakopoulou, E.; Gogou, A.; Papadopoulos, A.; Kanellopoulos, Th.D.; Rousakis, G.; Malinverno, E.; Triantaphyllou, M.V.; Lykousis, V.
Highlights: In the southern Cretan margin deep currents are very weak and particulate fluxes are low. Occasional high fluxes are due to lateral lithogenic inputs and sediment resuspension. The canyons were dormant during the observations period. Particle dynamics and fluxes in open slopes and canyons are similar. Coarse-grained sediments along the canyon axes point to episodic canyon activity. Abstract: The Samaria and Lithinon canyons at the southern Cretan margin (Eastern Mediterranean) were studied with respect to hydrography, deep currents, particle dynamics and settling fluxes by utilizing: (a) current-meter and sediment trap records from May 2005 to May 2006; and (b) hydrographic and optical measurements along with particulate matter and particulate organic carbon concentrations (PMC and POC, respectively) in two surveys (May and October 2005). The deep currents were very weak with mean velocity ∼3–4 cm s −1 and their direction was controlled by the local bottom topography. The entire area was characterized by very low PMC and POC, depicted both by transmissometry profiles and discrete bottle data. The fluxes of downward settling particles are comparable with the fluxes measured in the broader Eastern Mediterranean and hence point to an oligotrophic environment with low atmospheric and lateral inputs. A series of relatively high total mass fluxes (>1000 mg m −2 d −1 ) were recorded near the head of the Samaria canyon, at the trap closest to Crete, and was attributed to: (a) high temporal lithogenic inputs (mineral calcite) transferred to the sea by a small, intermittent stream flowing through the Samaria gorge, which was activated by short rainfall events and spring snowmelt; and (b) inputs of numerous coccoliths of E. huxleyi and calcite by shallow sediment resuspension generated by wind-induced waves. Apart from this local-scale event, there was very little evidence of matter transfer through the canyons, thus, during the one-year of observations, the canyons were dormant. Because of this lack of down-canyon transport during the study period, open slopes and canyons exhibited roughly similar characteristics in terms both of particle dynamics and fluxes. However, the presence of coarse-grained sediments along the canyon axes point to episodic canyon activity, occurring at unknown time scales and periodicity.